URGENSI PEMBATASAN NORMA PASAL 15 DAN 16 KUHP 2023 DALAM MENCEGAH POTENSI PELANGGARAN HAK KONSTITUSIONAL - pasaribu, cindy klara; Dr. Diki Zukriadi, S.H., M.H.. M.Kn. (LPPM Universitas Putera Batam, 2025)
The reformation of national criminal law through the enactment of Law Number 1 Year 2023 on the Criminal Code (KUHP) brings a number of new provisions, including the regulation of criminal acts in the preparatory stage as stated in Articles 15 and 16. These two articles expand the scope of punishment for acts that have not yet entered the stage of execution, but have been considered as preparation to commit a crime. The main problem that arises lies in the vagueness of the norms, especially regarding the absence of conceptual limits and objective indicators of what is meant by “preparation”. This vagueness creates the potential for abuse of authority by law enforcement officials and can threaten the constitutional rights of citizens, such as the right to legal certainty, the right to freedom of thought and expression, and the right not to be arbitrarily criminalized. This research aims to examine the urgency of restrictions and strict interpretation of the norm, in order to ensure that criminal law continues to function in the corridor of justice and protection of human rights. The method used is normative legal research with conceptual and statutory approaches.